ANALISIS KEGIATAN EKSTRAKURIKULER PASKIBRA DALAM MEMBANGUN KEPERCAYAAN DIRI SISWA DI SMA NEGERI 1 RASAU JAYA - Maisaroh Maisaroh; Sulistyarini Sulistyarini; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the paskibra extracurricular activities in building students' confidence in SMAN 1 Rasau Jaya. This study uses a qualitative approach with descriptive methods. The data source of this research is student affairs, post-liberal extracurricular trainers, and students who take the paskibra extracurricular activities at SMAN 1 Rasau Jaya. Data obtained through interview, observation, and documentation techniques. The data collection tool used is an observation guide, interview guide and documentation. The results showed that (1) the process of paskibra extracurricular activities in building the confidence of students in Rasau Jaya 1 Public High School can be said to build students' self-confidence because during the extracurricular activities the paskibra students practice by believing in their own abilities and do not expect help from others. There is no student who shows a conformist attitude to get recognition from the group. Students interact well with their fellow friends and coaches so they have good self-control. Students are always eager and persistent to continue to practice so students do not easily give up on fate and not depend on others. (2) The efforts of the paskibra trainer in building the confidence of students through paskibra extracurricular activities at Rasau Jaya 1 Public High School can be said to build students' self-confidence because through several training programs carried out by paskibra trainers such as on-the-spot movements, moving movements, walking movements, praise and punishment can build confidence, mentality, responsibility, courage, independence and discipline. Keywords: Extracurricular, Paskibra, Self Confidence, Students